Managerial perspectives on bio-technology international strategic alliances: The case of Malaysian firms - Abdul Ghani, Ahmad Bashawir; Subhan, Muhammad (2010)
This paper examines the views of Malaysian managing directors of prospective bio-tech international strategic alliances with European or US firms.It provides insights on the importance of contributions from a typical local (Malaysian) partner firm, as well as from a typical foreign (European or US) partner firm.It also uses a panel of specialists in order to classify independently two groups of firms: the most suitable and the least suitable to international strategic alliances. Several differences concerning the perceived importance of prospective contributions were identified between the two groups of local firms.